VIOLATION OF POLITENESS PRINCIPLE IN EDDIE HALL THE BEAST YOUTUBE CHANNEL VIDEO KAREN’S DINER EPISODE - Ramadhan, Inas; Sari'at Kurniati, Nur Utami; Rejeki, Sari (Universitas Pakuan, 2024)
This research has the purpose to inspect and identify the violation of the politeness principle in the video uploaded by Eddie Hall The Beast about Karen’s Diner. Based on the theory, the politeness principle has six forms, and this research has the purpose to identify the violations on each forms. The method used to complete this research is the descriptive method, a method that is used to describe the phenomenon. This research shows 10 data sentences that violate the politeness principle as the result of the entire research.